Overview And Review Of Small-Scale Industries In India (Journal of Namibian Studies : History Politics Culture, 2023)
India divides the SSIs into traditional and modern units. The three main categories of small-scale industries are manufacturing/production, ancillary, and service. In addition to these sectors, there are feeder industries and mining. These industries essentially need a lot of labor, however, the latter (i.e., modern units) include a broad range of complex items, including engineering and electrical equipment. Based on their "employment criteria," or the attributes of "hired labor" in the units, these two categorization types also differ from one another. This paper reflects overview and review of Small-Scale Industries in India.